The Burden of Pediatric Burns in Khyber Pakhtunkhwa Prevention and Management Strategies (Medical Forum Monthly, 2024)
Objective: The study aims to evaluate both prevention and management programs while measuring pediatric burn incidence throughout KP.Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Plastic Surgery & Burns Unit Khyber Teaching Hospital Peshawar from January 2019 to January 2020.Methods: This study collected data from 200 pediatric burns at various hospitals throughout KP using cross-sectional design. The gathered data included information about patient characteristics together with burn injury severity and treatment methods and treatment results. The research utilized descriptive statistics while the p-value assessed outcome significance.Results: Two hundred pediatric burn cases were examined for this analysis under which the average patient was 4.5 years old with a standard deviation of 2.1. A large number of these pediatric burn cases stemmed from hot liquids at 45% while flames accounted for 30%. Treatment practices involved wound care for 60% of patients in addition to skin grafts for 25% and the administration of antibiotics for 15%. The significance of the findings became clear because the p-value showed results at < 0.05 for the burn severity versus treatment outcome correlation. Children from five years of age and under showed both the most cases of burns and the longest treatment times.Conclusion: Pediatric burns represent a major public health problem in KP which requires both prevention measures and prompt medical help to decrease negative health effects and obtain better recovery success. The necessary public health solution includes improved safety education and increased healthcare infrastructure development.